A double-blind placebo-controlled randomized phase II trial assessing the activity and safety of regorafenib in non-adipocytic sarcoma patients previously treated with both chemotherapy and pazopanib. (February 2020) - Penel, Nicolas; Mir, Olivier; Wallet, Jennifer; Ray-Coquard, Isabelle; Le Cesne, Axel; Italiano, Antoine; Salas, Sebastien; Delcambre, Corinne; Bompas, Emmanuelle; Bertucci, François; Saada-Bouzid, Esma; Chaigneau, Loïc; et al.
Abstract: Background: Metastatic soft tissue sarcomas (STSs) management remains an unmet medical need. We assessed the activity and safety of regorafenib in patients with metastatic non-adipocytic STS who were previously treated with both chemotherapy and pazopanib. Patients and methods: This double-blind, placebo-controlled, multicenter comparative randomized phase II trial included patients with histologically proven advanced and inoperable STS. Patients receiving placebo were offered optional cross-over for centrally confirmed disease progression. Primary end-point was centrally reviewed Response Evaluation Criteria in Solid Tumours–based progression-free survival (PFS), analysed on the intent-to-treat data set. In total, 24 events were required for 90% power, hazard ratio (HR) = 0.33 (median PFS, 3.6 versus 1.2 months), and 1-sided α = 0.1 (ClinicalTrials.gov, NCT01900743 ). Results: From December 2015 to October 2017, 37 patients were randomized; 18 to regorafenib and 19 to placebo. Thirteen patients assigned to placebo switched to regorafenib after progression. Median follow-up was 27.2 months (95% confidence interval [CI]: 24.4–not reached). We observed a significant PFS benefit of regorafenib compared with placebo (adjusted HR = 0.33; 95% CI: 0.15–0.74; p = 0.0007 median PFS = 2.1 versus 1.1 months, respectively), and a large and nearly significant overall survival (OS) benefit despite the cross-over (adjusted HR = 0.49; 95% CI: 0.23–1.06; p = 0.007; median OS = 17.8 versus 8.2 months). Before cross-over, the most common grade III or higher adverse events were lymphopenia (5 versus 1, respectively), diarrhoea (4 versus 0), dyspnoea (3 versus 1), skin toxicity (3 versus 0), arterial hypertension (2 versus 0), and increased transaminases (2 versus 0). Conclusion: The present study demonstrated a meaningful clinical anti-tumour activity with regorafenib in heavily pre-treated patients with non-adipocytic STS. Highlights: This placebo-controlled double-blind randomized phase II trial shows that regorafenib is active in patients with advanced non-adipocytic soft tissue sarcoma. The progression-free survival is significantly improved compared with placebo even after prior treatment with pazopanib. Despite cross-over, we have observed overall survival improvement (8.2 versus 17.8 months).